Determinants of new products innovation in Ghanaian SMEs sector - Thomas Bilaliib Udimal; Zhuang Jincai; Abdul-Aziz Ibn Musah; Cheng Hua (Journal of Global Entrepreneurship Research, 2019)
The paper analyzes the determinants of new products innovation in the SMEs sector. The study focused on types of innovation funding and sources of innovation funding. Five-hundred and fifty (550) SME owners were randomly selected for the study. Information was sourced through the use of questionnaires. Tobit model was used for the analysis. Sales value of new products was used a proxy for new products innovation. The determinants were grouped into two types thus innovation expenditure and sources of innovation expenditure. Sources of innovation expenditure have significant influence on new products innovation. From the finding foreign capital, government tax credit, and subsidies had significantly influence on new products innovation. SMEs specific attributes such as patent and having overseas partners influence new product innovation. Policies and programs geared towards government tax credit, subsidies, patent rights and inflow of foreign capital into SME sector should be encouraged since they have the potential of promoting product innovation in the sector.
Keywords: 650; Innovation expenditure; Sources of innovation expenditure; New products innovation; SMEs finance